La mise en image des magazines. Le choix crucial et victorieux des utilitaristes anglais dans les années 1830 - Jean-Pierre Bacot (Revue LISA)
In this article, I consider the birth of the first illustrated magazine in the context of editorial trends in England in the 1830s, a period of political and social change. Studying the relationship between the Penny Magazine and its competitors allows me to question the choices made by some political and religious interests concerning the use of images. I also show how the wish to diffuse an encyclopaedist culture to as many people as possible resulted in both the extension of readership towards the middle classes and a secularisation of knowledge. Finally, the article insists on the supranational character of the cultural imaginary that was constructed by magazines published in various countries, in the same format and with very similar content.